Quality of Colonoscopy Performed in Rural Practice: Experience From the Clinical Outcomes Research Initiative and the Oregon Rural Practice-based Research Network - Holub, Jennifer L. (J Rural Health, 2017)
PURPOSE: Colon cancer screening is effective. To complete screening in 80% of individuals over age 50 years by 2018 will require adequate colonoscopy capacity throughout the country, including rural areas, where colonoscopy providers may have less specialized training. Our aim was to study the quality of colonoscopy in rural settings. METHODS: The Clinical Outcomes Research Initiative (CORI) and the Oregon Rural Practice-based Research Network (ORPRN) collaborated to recruit Oregon rural practices to submit colonoscopy reports to CORI’s National Endoscopic Database (NED). Ten ORPRN sites were compared to non-ORPRN rural (n=11) and non-rural (n=43) sites between January 2009 and October 2011. Established colonoscopy quality measures were calculated for all sites. RESULTS: No ORPRN physicians were gastroenterologists compared with 82% of non-rural physicians. ORPRN practices reached the cecum in 87.4% of exams compared with 89.3% of rural sites (P = .0002) and 90.9% of non-rural sites (P < .0001). Resected polyps were less likely to be retrieved (84.7% vs 91.6%; P < .0001) and sent to pathology (77.1% vs 91.3%; P < .0001) at ORPRN practices compared to non-rural sites. The overall polyp detection (39.0% vs 40.3%) was similar (P = .217) between ORPRN and non-rural practices. Of exams with polyps, the rate for largest polyp on exam 6–9 mm was 20.8% at ORPRN sites, compared to 26.8% at non-rural sites (P < .0001), and for polyps >9mm 16.6% vs 18.7% (P = .106). CONCLUSION: ORPRN sites performed well on most colonoscopy quality measures, suggesting that high-quality colonoscopy can be performed in rural settings.